PENGARUH KONSELING TERHADAP SELF STIGMA PASIEN HIV/AIDS DENGAN PENDEKATAN TEORI LAWRENCE GREEN - Imam Ajib Ispurnawan; Noer Saudah; Imam Zainuri (Jurnal EDUNursing, 2021)
Abstract The stigma that occurs in society against people with HIV and AIDS has an impact on sufferers to stigmatize themselves (Self Stigma). Negative self-acceptance which causes a decrease in self-esteem and self-efficacy so that it affects the individual's belief to be able to recover. The purpose of this study was to analyze the effect of counseling on self-stigma of patients with the Lawrence green theory approach. The research design was a pretest-posttest control group design with a sample size of 40 respondents selected by purposive sampling technique. The instrument used is a questionnaire. Counseling treatment of respondents using the module. The statistical tests used were paired t-test and independent t-test. The test results showed that the treatment group was 0.000 and the control group was 0.104. Correlation coefficient 0.600. The independent t test value of 0.001 means that there is a difference in the average number of self-stigma in the treatment group and the average in the control group after counseling. Counseling with Lawrence Green's theoretical approach can reduce self-stigma so that HIV/AIDS patients think positively about themselves, do not withdraw from the environment and are willing to behave in therapy for their own healing. Keywords: self stigma, HIV/AIDS, counseling, lawrence green